Silicon-carbon material, preparation method thereof, secondary battery and electric device
By using silicon-carbon composite particles containing porous carbon materials, nano-silicon grains, silicon carbide material layer and carbon clad layer in lithium-ion batteries, the problem of degradation of cyclic performance caused by volume expansion of silicon materials is solved, and better battery cyclability and stability are achieved.
Patent Information
- Application Number
- CN202410302266.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-15
- Publication Date
- 2025-04-15
AI Technical Summary
The existing silicon-carbon anode material has deteriorated circulation performance due to the volume expansion of silicon material in lithium-ion batteries, and the existing improved methods have not effectively solved the problem.
Silicon-carbon composite particles including porous carbon materials, nano-silicon grains, silicon carbide material layer and carbon cladding layer are used to limit the expansion of silicon material through the through-holes, and the reaction probability of the silicon material with the electrolyte is reduced through the silicon carbide material layer and carbon cladding layer.
Effectively control the expansion degree of silicon material, reduce the probability of side reaction between silicon material and electrolyte, and improve the cyclability of the battery.
Smart Images

Figure CN119833588A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a silicon-carbon material and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] Silicon has the highest specific capacity of all known negative electrode materials, reaching 4200mAh / g. However, the silicon-lithium alloy formed by pure silicon during the charging process in lithium-ion batteries will cause the negative electrode material to undergo a huge volume expansion, with an expansion rate of 300%, causing the negative electrode material to collapse and pulverize, destroying the battery's cycle performance. Silicon-carbon composites can effectively reduce the volume effect of negative electrode materials. Currently, the cycle performance of existing silicon-carbon negative electrode materials has been improved to a certain extent, but it still needs to be further optimized to meet the needs of power batteries. Summary of the invention
[0003] In view of the above problems, the present application provides a silicon-carbon material and a preparation method thereof, a secondary battery and an electrical device, which are beneficial to improving the cyclability of the battery.
[0004] In a first aspect, the present application provides a silicon-carbon material, including: a silicon-carbon composite particle, wherein the silicon-carbon composite particle includes:
[0005] Porous carbon materials: have through holes;
[0006] Nano silicon grains: located in the through holes; the grain size of the nano silicon grains is not less than the average pore size of the porous carbon material;
[0007] The silicon carbide material layer is at least partially located on the wall of the through hole.
[0008] The silicon-carbon material provided by the present application includes silicon-carbon composite particles, which include porous carbon materials, and the porous carbon materials have through holes, wherein the through holes include macropores, mesopores and micropores for depositing silicon materials, and the silicon materials are deposited in the through holes of the porous carbon materials. On the one hand, the through holes can limit the expansion of the silicon materials, and on the other hand, since the through holes are connected to the closed holes, the electrolyte has a certain degree of physical isolation, and the probability of side reactions caused by direct contact between the silicon materials and the electrolyte can also be reduced. The present application selects to form nano-silicon grains with a certain suitable particle size in the through holes, and the nano-silicon grains with the suitable particle size are stacked to form nano-silicon particles, and the nano-silicon particles are further stacked along the inner wall of the through hole to form a layered or sheet-like film, and a silicon carbide material layer is generated where the layered or sheet-like film is in direct contact with the inner wall of the through hole. This arrangement can not only reduce the probability of its reaction with the electrolyte, but also control the expansion rate of the silicon material, because the expansion of the silicon material is not only limited by the through holes, but also by the silicon carbide material layer. Therefore, the silicon-carbon material provided in this application reduces the probability of side reactions between the silicon material and the electrolyte while controlling the expansion degree of the silicon material during the process of lithium ion insertion and extraction, thereby improving the cyclability of the battery to a certain extent from multiple aspects, such as forming nano-silicon grains with a certain suitable particle size, physical isolation, physical confinement, etc.
[0009] In some embodiments of the present application, the grain size of the nano-silicon grains is d1, and the average pore size of the porous carbon material is d2, satisfying: d1 / d2=1-15.
[0010] In some embodiments of the present application, the grain size of the nano-silicon grains is d1, and the average pore size of the porous carbon material is d2, satisfying: d1 / d2=2-10.
[0011] In some embodiments of the present application, the grain size of the nano-silicon grains is d1, d1 ≥ 5 nm;
[0012] and / or;
[0013] The average pore size of the porous carbon material is d2, and d2 is 1.0 nm to 5.0 nm.
[0014] In some embodiments of the present application, the grain size of the nano-silicon grains is d1, and d1 is 5 nm to 20 nm;
[0015] and / or;
[0016] The average pore size of the porous carbon material is d2, and d2 is 1.5nm to 5.0nm.
[0017] In some embodiments of the present application, the silicon-carbon composite particles include closed pores, and the pore volume of the closed pores is smaller than the pore volume of the through pores.
[0018] In some embodiments of the present application, the silicon-carbon composite particles include closed pores, the pore volume of the closed pores is V1, and the pore volume of the through pores is V2, satisfying: V2 / V1=5-24.
[0019] In some embodiments of the present application, the silicon-carbon composite particles include closed pores, the pore volume of the closed pores is V1, and the pore volume of the through pores is V2, satisfying: V2 / V1=7-16.
[0020] In some embodiments of the present application, the pore volume of the closed pore is V1, and V1 is 0.04 cm 3 / g~0.16cm 3 / g;
[0021] and / or;
[0022] The pore volume of the through hole is V2, and V2 is 0.3 cm 3 / g~1.5cm 3 / g.
[0023] In some embodiments of the present application, the through pores include micropores, mesopores and macropores, and based on the total volume of the through pores, the volume ratio between the micropores, mesopores and macropores is (40% to 95%): (5% to 50%): (0 to 15%).
[0024] In some embodiments of the present application, the silicon carbide material layer is located between the through hole and the nano-silicon grains, wherein one side of the silicon carbide material layer is connected to the inner wall of the through hole, and the other side is connected to the nano-silicon grains.
[0025] In some embodiments of the present application, the thickness of the silicon carbide material layer is less than 0.7 nm.
[0026] In some embodiments of the present application, the silicon-carbon material further comprises a carbon coating layer, which is disposed along the outer surface of the porous carbon material. The carbon coating layer can reduce the probability of the nano-silicon grains being in contact with the outside air and thus being oxidized, and can also reduce the probability of the nano-silicon grains being in contact with the electrolyte and reacting.
[0027] In some embodiments of the present application, the porous carbon material comprises porous carbon particles, and the porous carbon particles meet the following conditions:
[0028] (1.1) The volume distribution particle size of the porous carbon particles satisfies: Dv50 is 3.0 μm to 6.5 μm; Dv90 is 13.5 μm to 18.5 μm; Dv10 is 0.9 μm to 2.5 μm;
[0029] (1.2) The specific surface area of porous carbon particles is 900 m 2 / g~1550m 2 / g;
[0030] (1.3) The tap density of porous carbon particles is 0.22 g / cm 3 ~0.48g / cm 3 ;
[0031] (1.4) The compacted density of 5 tons of porous carbon particles is 0.45 g / cm 3 ~0.80g / cm 3 .
[0032] In some embodiments of the present application, the porous carbon material comprises porous carbon particles, and the porous carbon particles satisfy at least one of the following:
[0033] (2.1) The volume distribution particle size of the porous carbon particles satisfies: Dv50 is 3.5 μm to 6.0 μm; Dv90 is 14.0 μm to 18.0 μm; Dv10 is 1.0 μm to 2.0 μm;
[0034] (2.2) The specific surface area of porous carbon particles is 1000m 2 / g~1500m 2 / g;
[0035] (2.3) The tap density of porous carbon particles is 0.25 g / cm 3 ~0.45g / cm 3 ;
[0036] (2.4) The compacted density of 5 tons of porous carbon particles is 0.50 g / cm 3 ~0.75g / cm 3 .
[0037] In some embodiments of the present application, based on the total mass of the silicon-carbon material, the mass percentage content of silicon in the silicon-carbon material is w 硅 , satisfying: w 硅 It is 38.0% to 48.0%.
[0038] In some embodiments of the present application, the silicon-carbon composite particles meet the following conditions:
[0039] (3.1) The volume distribution particle size of the silicon-carbon composite particles satisfies: (Dv90-Dv10) / Dv50 is 1.2 to 2.8;
[0040] (3.2) The specific surface area of silicon-carbon composite particles is 3.0 m 2 / g~12.0m 2 / g;
[0041] (3.3) The tap density of silicon-carbon composite particles is 0.5 g / cm 3 ~1.0g / cm 3;
[0042] (3.4) The compacted density of 5 tons of silicon-carbon composite particles is 0.80 g / cm 3 ~1.1g / cm 3 .
[0043] In some embodiments of the present application, the silicon-carbon composite particles satisfy at least one of the following:
[0044] (4.1) The volume distribution particle size of the silicon-carbon composite particles meets the following requirements: Dv50 is 3.5 μm to 9.0 μm; Dv90 is 14.0 μm to 21.0 μm; Dv10 is 0.9 μm to 3.0 μm;
[0045] (4.2) The specific surface area of silicon-carbon composite particles is 5.0 m 2 / g~10.0m 2 / g;
[0046] (4.3) The tap density of silicon-carbon composite particles is 0.6 g / cm 3 ~0.8g / cm 3 ;
[0047] (4.4) The compacted density of 5 tons of silicon-carbon composite particles is 0.90 g / cm 3 ~1.05g / cm 3 .
[0048] In some embodiments of the present application, the properties of the silicon-carbon composite particles meet the following requirements:
[0049] The powder resistivity of silicon-carbon composite particles at 4Mpa is 1.30Ω·cm to 3.80Ω·cm;
[0050] and / or;
[0051] The lithium removal capacity of the silicon-carbon composite particles is 1300mAh / g to 1500mAh / g, and the first coulombic efficiency is 77% to 81%;
[0052] and / or;
[0053] In the dQ / dV curve of silicon-carbon composite particles, I1 is the peak intensity near 0.3V~0.35V; I2 is the peak intensity near 0.43V~0.50V; it satisfies: I1 / I2=1.4~1.8; the dQ / dV curve of silicon-carbon composite particles includes silicon-carbon composite particles as the positive electrode active material, metal lithium sheets as the counter electrode, assembled to form a CR2430 button battery, at 25°C, the charge and discharge voltage is 0.005V~2.0V, and the charge and discharge capacity and the working electrode potential are obtained by differential processing.
[0054] The second aspect of the present application is to provide a method for preparing the silicon-carbon negative electrode material according to the first aspect, comprising:
[0055] providing a porous carbon substrate;
[0056] A silicon source is introduced into the porous carbon substrate to generate a porous carbon material comprising nano-silicon grains and a silicon carbide material layer;
[0057] A carbon source is introduced into a porous carbon material including nano-silicon grains and a silicon carbide material layer to generate a silicon-carbon material including a carbon coating layer.
[0058] In some embodiments of the present application, the reaction conditions for generating a porous carbon material comprising nano-silicon grains and a silicon carbide material layer are as follows:
[0059] (5.1) The reaction temperature is 500°C to 700°C, and the silicon source is introduced for 3h to 42h;
[0060] (5.2) The silicon source comprises a silicon source gas and a diluent gas, wherein the volume fraction of the silicon source gas is 15% to 95%; the silicon source gas comprises one or both of monosilane and disilane;
[0061] (5.3) The ventilation volume of the silicon source is 0.2L / min~1.5L / min.
[0062] In some embodiments of the present application, the porous carbon substrate comprises carbon, oxygen and nitrogen, and the mass ratio of carbon to oxygen and nitrogen is (94% to 97%): (2% to 4%): (1% to 2%);
[0063] And / or; the ash content of the porous carbon substrate is ≤0.5%.
[0064] The third aspect of the present application is to provide a secondary battery, which comprises a negative electrode plate, and the negative electrode plate comprises the silicon-carbon material described in the first aspect or the silicon-carbon material prepared by the preparation method described in the second aspect.
[0065] A fourth aspect of the present application is to provide an electrical device, which comprises the secondary battery described in the third aspect.
[0066] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0068] Figure 1 A schematic diagram of the battery structure of some embodiments of the present application;
[0069] Figure 2 This is a schematic diagram of the exploded structure of batteries in some embodiments of the present application;
[0070] Figure 3 A schematic diagram of a vehicle structure of some embodiments of the present application;
[0071] Figure 4 A schematic diagram of the structure of a battery pack according to some embodiments of the present application;
[0072] Figure 5 Electron microscope images of silicon-carbon materials prepared for some embodiments of the present application;
[0073] Figure 6 A schematic diagram of the structure of silicon-carbon materials prepared in some embodiments of the present application;
[0074] Figure 7 X-ray photoelectron spectroscopy analysis spectra of silicon-carbon materials were obtained for some embodiments of the present application.
[0075] Figure 8 Further magnified electron microscope images of silicon-carbon materials prepared for some embodiments of the present application.
[0076] Fig. 9 Transmission electron microscopy images of carbon coatings of silicon-carbon materials prepared for some embodiments of the present application.
[0077] Fig.10 X-ray diffraction patterns of silicon-carbon materials obtained for some embodiments of the present application;
[0078] Fig.11 A dQ / dV curve of a discharge curve of a silicon-carbon material is obtained for some embodiments of the present application.
[0079] The reference numerals in the specific implementation manner are as follows:
[0080] 10000, vehicles;
[0081] 1000, battery; 2000, controller; 3000, motor;
[0082] 100. Battery cell;
[0083] 200, box body; 210, first part; 220, second part;
[0084] 10. Secondary battery;
[0085] 101, housing; 102, electrode assembly; 103, cover plate;
[0086] 1. Silicon-carbon composite particles; 1a. Porous carbon material; 1b. Nano-silicon grains; 1c. Remaining closed pores; 1d. Silicon carbide material layer. DETAILED DESCRIPTION
[0087] Hereinafter, the silicon-carbon material and its preparation method, the secondary battery and the electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0088] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0089] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0090] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0091] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0092] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or included, or may only include or include the listed components.
[0093] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0094] If not otherwise specified, in this application, the terms "first", "second", etc. are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.
[0095] Unless otherwise specified, in this application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple sheets" refers to more than two sheets (including two sheets).
[0096] Unless otherwise specified, the orientations or positional relationships indicated by technical terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", and "circumferential" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present application.
[0097] The specific capacity of silicon is the highest among all known negative electrode materials, reaching 4200mAh / g. However, the silicon-lithium alloy formed by pure silicon during the charging process in lithium-ion batteries will cause a huge volume expansion of the negative electrode material, with an expansion rate of 300%, causing the negative electrode material to collapse and pulverize, destroying the safety and cycle performance of the battery. Silicon-carbon composites can effectively reduce the volume effect of negative electrode materials. Specifically, silicon-carbon composites involve mixing nano-silicon with carbon materials. By reducing the particle size of silicon-based materials to the nanometer level, more voids can be used to buffer the stress and deformation generated by silicon during the process of lithium ion insertion and extraction. However, as the particle size of silicon-based materials decreases, they are more likely to react with electrolytes that slowly penetrate into the surface of silicon-based materials, thereby accelerating cycle attenuation.
[0098] In order to solve the above problems, the prior art discloses methods including developing new electrolytes or forming physical isolation on the surface of silicon-based materials to reduce the probability of side reactions. However, these improvements are not ideal.
[0099] If the particle size of the silicon-based material can be increased to a certain extent, but not to an unlimited extent, and the probability of side reactions between the silicon-based material and the electrolyte can be reduced while controlling the degree of expansion of the silicon-based material during the deintercalation and extraction of lithium ions, the cyclability of the battery can be improved to a certain extent.
[0100] Based on the above considerations, in order to solve the technical problem of accelerated cycle attenuation due to side reactions between silicon-based materials and electrolytes in batteries, a silicon-carbon material and its preparation method, a secondary battery and an electrical device were obtained according to the above design concept and related experimental research.
[0101] First, the present application discloses a silicon-carbon material, which includes silicon-carbon composite particles, which include porous carbon material, nano-silicon grains, a silicon carbide material layer and a carbon coating layer. The porous carbon material has through holes, the nano-silicon grains are located in the through holes, and the silicon carbide material layer is located between the through holes and the nano-silicon grains; the grain size of the nano-silicon grains is not less than the average pore size of the porous carbon material; and the carbon coating layer is arranged along the outer surface of the porous carbon material.
[0102] The silicon-carbon material provided by the present application includes silicon-carbon composite particles, which include porous carbon materials, and the porous carbon materials have through holes, wherein the through holes include macropores, mesopores and micropores for depositing silicon materials, and the silicon materials are deposited in the through holes of the porous carbon materials. On the one hand, the through holes can limit the expansion of the silicon materials, and on the other hand, due to the physical isolation of the through holes to a certain extent on the electrolyte, the probability of side reactions caused by direct contact between the silicon materials and the electrolyte can be reduced. The present application selects to form nano-silicon grains with a certain suitable particle size in the through holes, and the nano-silicon grains with the suitable particle size are stacked to form nano-silicon particles, and the nano-silicon particles are further stacked along the inner wall of the through holes to form a layered or sheet-like film, and the layered or sheet-like film is directly in contact with the inner wall of the through hole. A silicon carbide material layer is generated in the area. This arrangement can not only reduce the probability of its reaction with the electrolyte, but also control the expansion rate of the silicon material, because the expansion of the silicon material is not only limited by the through holes, but also by the silicon carbide material layer. In addition, a carbon coating layer is formed on the outside of the porous carbon material, which can reduce the probability of the nano-silicon grains being in contact with the outside air and then being oxidized, and can reduce the probability of the nano-silicon grains being in contact with the electrolyte. Therefore, the silicon-carbon material provided by this application reduces the probability of side reactions between the silicon material and the electrolyte under the premise of controlling the expansion degree of the silicon material during the process of lithium ion extraction, thereby improving the cyclability of the battery to a certain extent.
[0103] The silicon-carbon material provided in the present application is used to make a negative electrode plate and is applied to a battery, thereby improving the performance of the battery, such as improving the cyclability at a certain capacity, thereby increasing the user experience. The battery may include an outer packaging. The outer packaging can be used to encapsulate the above-mentioned electrode assembly and electrolyte. The outer packaging of the battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.
[0104] The present application has no particular limitation on the shape of the battery, which may be cylindrical, square or any other shape. For example, Figure 1 The secondary battery 10 is a square structure as an example.
[0105] According to some embodiments of the present application, Figure 2, the outer packaging may include a shell 101 and a cover plate 103. Among them, the shell 101 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 101 has an opening connected to the receiving cavity, and the cover plate 103 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 102 through a winding process or a lamination process. The electrode assembly 102 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 102. The number of electrode assemblies 102 contained in the secondary battery 10 can be one or more, and those skilled in the art can select according to specific actual needs.
[0106] The electrode assembly provided in the present application is applied to batteries to improve battery performance. The battery can be used as a power source for an electrical device or as an energy storage unit for an electrical device. The electrical device is applied to the power field, such as mobile devices (such as mobile phones, laptop computers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but not limited to the above-mentioned fields.
[0107] For the convenience of explanation, some embodiments of the present application are described by taking a vehicle as an example of an electrical device.
[0108] Please refer to Figure 3 , Figure 3 A schematic diagram of the structure of a vehicle 10000 provided for some embodiments of the present application. The vehicle 10000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 1000 is provided inside the vehicle 10000, and the battery 1000 may be provided at the bottom, head or tail of the vehicle 10000. The battery 1000 may be used to power the vehicle 10000, for example, the battery 1000 may be used as an operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000, and the controller 2000 is used to control the battery 1000 to power the motor 3000, for example, for the starting, navigation and working power requirements of the vehicle 10000 during driving.
[0109] In some embodiments of the present application, the battery 1000 can not only serve as the operating power source of the vehicle 10000, but also serve as the driving power source of the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.
[0110] Please refer to Figure 4 , Figure 4The exploded diagram of the battery 1000 provided in some embodiments of the present application. The battery 1000 includes a housing 200 and a battery cell 100. Conventional battery cells include primary batteries or secondary batteries. The present application specifically protects secondary batteries. The battery cell 100 is accommodated in the housing 200. The housing 200 is used to provide a storage space for the battery cell 100. The housing 200 can adopt a variety of structures.
[0111] In some embodiments, the box body 200 may include a first part 210 and a second part 220, the first part 210 and the second part 220 cover each other, and the first part 210 and the second part 220 jointly define a storage space for accommodating the secondary battery 100. The second part 220 may be a hollow structure with one end open, and the first part 210 may be a plate-like structure, and the first part 210 covers the open side of the second part 220, so that the first part 210 and the second part 220 jointly define a storage space; the first part 210 and the second part 220 may also be hollow structures with one side open, and the open side of the first part 210 covers the open side of the second part 220. Of course, the box body 200 formed by the first part 210 and the second part 220 may be in various shapes, such as a cylinder, a cuboid, etc.
[0112] In the battery 1000, there may be multiple battery cells 100, and the multiple battery cells 100 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 100 are both connected in series and in parallel. The multiple battery cells 100 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 100 is accommodated in the box 200; of course, the battery 1000 may also be a battery 1000 module formed by connecting multiple battery cells 100 in series, in parallel, or in a mixed connection, and then the multiple battery 1000 modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 200. The battery 1000 may also include other structures, for example, the battery 1000 may also include a busbar component for realizing electrical connection between the multiple battery cells 100.
[0113] Silicon Carbon Materials
[0114] In some embodiments, the present application discloses a silicon-carbon material, which includes silicon-carbon composite particles, which include porous carbon material, nano-silicon grains, a silicon carbide material layer and a carbon coating layer. The porous carbon material has through holes, the nano-silicon grains are located in the through holes, and the silicon carbide material layer is located on the through hole walls; the grain size of the nano-silicon grains is not less than the average pore size of the porous carbon material.
[0115] The silicon-carbon composite particles in the present application include particles mainly composed of silicon and carbon. The composite method here includes any conventional composite form in the art.
[0116] The nano silicon grains in the present application include silicon grains with a particle size of nanometer level, and the formation method of the nano silicon grains includes but is not limited to chemical vapor deposition, physical vapor deposition or atomic layer deposition.
[0117] The through holes in the present application include through holes that are connected to the outside, such as macropores, mesopores and micropores used to deposit silicon materials. Nano silicon grains are distributed and stacked along the inner wall of the through holes to form silicon materials with layered or sheet-like films.
[0118] The grain size of the nano silicon grains in the present application is not less than the average pore size of the porous carbon material. The average pore size of the porous carbon material in the present application includes any conventional method in the art. For example, the distribution of each hole is tested by a conventional test instrument in the art, and the number of each hole is obtained by statistics, and then the average pore size is calculated by a mathematical function. The pore volume and specific surface area of the porous carbon material can also be obtained by using adsorption and desorption isotherms. According to the model of the relevant pores, the pore volume is divided by the specific surface area and multiplied by the model coefficient to obtain the average pore size; for example, the test instrument is ASAP2460-physical adsorption analyzer, and the porous carbon material sample after drying and degassing is placed in liquid nitrogen, and different test pressures are adjusted. The adsorption amount of nitrogen is measured respectively, and the adsorption and desorption isotherms are drawn, and then the pore volume and specific surface area of the porous carbon material are obtained according to the adsorption and desorption isotherms, and then the average pore size of the porous carbon material is calculated. The nano silicon grains of the present application include silicon grains with a particle size of nanometer level, and the crystal form of the nanometer-level silicon grains includes the conventional crystal structure in the art. The grain size of the nano silicon grains includes the grain size distribution measured by a testing instrument such as an X-ray diffractometer and then obtained by statistics or the grain size distribution measured by a transmission electron microscope and then obtained by statistics.
[0119] The grain size of the nano silicon grains of the present application is not less than the average pore size of the porous carbon material. In some embodiments of the present application, the grain size of the nano silicon grains is d1, and the average pore size of the porous carbon material is d2, satisfying d1≥d2. This is because the nano silicon grains are distributed and stacked along the through holes of the porous carbon material, so the average pore size of the porous carbon material does not affect the stacking process of the nano silicon grains, but can limit the result of the stacking of the nano silicon grains, that is, limit the expansion of the silicon material. The present application selects nano silicon grains with a certain suitable particle size to be distributed in the through holes of the porous carbon material. Under the premise of controlling the expansion degree of the silicon material during the process of lithium ion extraction, the probability of side reactions between the silicon material and the electrolyte is reduced, and the cyclability of the battery is also improved to a certain extent.
[0120] The formation of the silicon carbide material layer of the present application is affected by the preparation conditions. For example, during the growth of silicon grains, the silicon grains close to the inner wall of the through hole are easy to contact the wall and react to form a silicon carbide material layer. The hardness of the silicon carbide material layer is greater than that of the silicon material, and it can limit the degree of outward expansion when the silicon material expands. Therefore, the silicon-carbon material provided by the present application reduces the probability of side reactions between the silicon material and the electrolyte under the premise of controlling the expansion degree of the silicon material during the process of lithium ion extraction, and improves the cyclability of the battery to a certain extent.
[0121] In some embodiments of the present application, the grain size d1 of the nano-silicon grains and the average pore size d2 of the porous carbon material satisfy: d1 / d2=1-15.
[0122] In some embodiments of the present application, the grain size d1 of the nano-silicon grains and the average pore size d2 of the porous carbon material satisfy: d1 / d2=2-10.
[0123] The grain size d1 of the nano-silicon grains provided in the present application cannot be unlimitedly larger than the average pore size d2 of the porous carbon material, otherwise it is not conducive to the formation of nano-silicon grains and may affect the performance of the battery, such as the need for lithium ions to complete the deintercalation process from the silicon material with a relatively large size, thereby affecting the rate capability of the battery. The present application selects to control d1 / d2=1-15, which, on the one hand, facilitates the efficient formation of nano-silicon grains in the through holes of the porous carbon material, and on the other hand, does not affect the comprehensive performance of the battery, such as cyclability, rate capability, etc. In these embodiments, the present application provides that the relationship between the grain size d1 of the nano-silicon grains and the average pore size d2 of the porous carbon material satisfies, including but not limited to, d1 / d2=1, d1 / d2=2, d1 / d2=3, d1 / d2=4, d1 / d2=5, d1 / d2=6, d1 / d2=7, d1 / d2=8, d1 / d2=9, d1 / d2=10, d1 / d2=11, d1 / d2=12, d1 / d2=13, d1 / d2=14, d1 / d2=15.
[0124] In some embodiments of the present application, the grain size d1 of the nano-silicon grains is ≥5 nm.
[0125] In some embodiments of the present application, the grain size d1 of the nano-silicon grains is 5 nm to 20 nm.
[0126] In some embodiments of the present application, the grain size d1 of the nano-silicon grains is 5 nm to 15 nm.
[0127] The nano silicon grains in the present application include silicon grains of nanometer size, and the crystal form of the nano silicon grains includes a conventional crystal structure in the art. The grain size of the nano silicon grains includes the size calculated by the Scherrer formula using an X-ray diffraction pattern known in the art, and the silicon grain size is a statistical size.
[0128] The present application selects a grain size of nano silicon grains ≥ 5nm, because the grain size of silicon grains cannot be too small, otherwise it is easy to increase the probability of side reactions. Silicon grains with this size are convenient and efficient to form in the through hole, and at the same time, the probability of reaction with the electrolyte can be reduced. At the same time, the grain size of nano silicon grains cannot be increased indefinitely. On the one hand, it is limited by the preparation process. On the other hand, nano silicon grains with larger grain sizes increase the expansion degree and probability of silicon materials in the process of lithium ion extraction and insertion, and are not conducive to the diffusion of lithium ions in the process of lithium ion extraction and insertion. Therefore, the present application selects the grain size d1 of nano silicon grains to be 5nm to 20nm. The present application discloses in these embodiments that the grain size d1 of nano silicon grains includes but is not limited to any one of 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm or any one of the above range values.
[0129] In some embodiments of the present application, the average pore diameter d2 of the porous carbon material is 1.0 nm to 5.0 nm.
[0130] In some embodiments of the present application, the average pore diameter d2 of the porous carbon material is 1.5 nm to 5.0 nm.
[0131] The present application selects a porous carbon material with an average pore size of 1.0 nm to 5.0 nm, which facilitates the efficient formation of silicon material in the through holes and also facilitates the subsequent restriction of silicon material expansion.
[0132] The present application discloses in these embodiments that the average pore diameter of the porous carbon material is any one of 1.0 nm, 1.5 nm, 2.0 nm, 3.0 nm, 4.0 nm, 4.5 nm, 5.0 nm or any one of the values satisfying the above ranges.
[0133] In some embodiments of the present application, the silicon-carbon composite particles include closed pores, and the pore volume of the closed pores is smaller than the pore volume of the through pores.
[0134] The closed pores of the present application include pores in the silicon-carbon composite particles that are not connected to the outside world. The closed pores include the closed pores possessed by the porous carbon material itself, and also include a certain number of closed pores formed in the through holes after the nano-silicon grains are formed in the through holes. Based on the above-mentioned through holes and the silicon carbide material layer restricting the expansion of the silicon material, these partial closed pores can further provide a slow-release space for the expansion of the silicon material, thereby alleviating the expansion of the silicon-carbon material.
[0135] In some embodiments of the present application, the pore volume of the closed pores is V1, and the pore volume of the through pores is V2, satisfying V1<V2.
[0136] The pore volume of the present application is also called the pore volume, wherein the pore volume V1 of the closed pores can be calculated by using the calculation formula (I) and combining the relevant test results: V1 = 1 / ρ 真 -1 / (w 硅 ×ρ 硅 +w 碳 ×ρ 碳 ); formula (I).
[0137] In formula (I), ρ 真 is the test true density of silicon carbon material, w 硅 is the mass percentage of silicon in the silicon-carbon material, w 碳 is the mass percentage of carbon in silicon-carbon material, ρ 硅 is the theoretical true density of silicon, ρ 碳 is the theoretical true density of carbon. 硅 It includes the mass percentage of silicon element based on the total mass of silicon-carbon material, and w 碳 Contains the mass percentage of carbon element based on the total mass of silicon-carbon material. 硅 is the theoretical true density of silicon, and its specific value is 2.34g / cm 3 , ρ 碳 is the theoretical true density of carbon, and its specific value is 2.26g / cm 3 ρ 真is the test true density of silicon-carbon material, which can be obtained by testing with reference to GB / T24586-2009. The pore volume of the through-holes of the porous carbon material of the present application can also be the pore volume of the porous carbon material, that is, the pore volume of the porous carbon material, which includes the measurement using instruments and methods known in the art, for example, it can be tested with reference to GB / T21650.2-2008. The testing instrument can be the TRISTAR II3020 specific surface area and porosity analyzer of Micromeritics, USA. The through-holes of the present application are mainly used to deposit silicon materials, while the closed holes are used to provide a slow-release space when the silicon material expands, so that the closed holes occupy a certain pore volume to reduce the amount of nano-silicon grains formed inside the porous carbon material, but it does not affect the use of nano-silicon grains as negative electrode active materials. Therefore, the present application selects the pore volume V1 of the closed holes to be smaller than the pore volume V2 of the through-holes.
[0138] In some embodiments of the present application, the pore volume V1 of the closed pores and the pore volume V2 of the through pores satisfy:
[0139] V2 / V1=5~24.
[0140] The present application selects V2 / V1=5-24 to explore obtaining nano-silicon grains with suitable size and formation amount, and improves the cyclability of the battery by reducing the reaction between the nano-silicon grains and the electrolyte without affecting the battery capacity.
[0141] In some embodiments of the present application, the pore volume V1 of the closed pores and the pore volume V2 of the through pores satisfy:
[0142] V2 / V1=7~16.
[0143] The present application further improves the cyclability of the battery by selecting V2 / V1=7-16.
[0144] In some embodiments, the present application also specifically defines any one of V2 / V1=5, V2 / V1=6, V2 / V1=7, V2 / V1=8, V2 / V1=9, V2 / V1=10, V2 / V1=11, V2 / V1=12, V2 / V1=13, V2 / V1=14, V2 / V1=15, V2 / V1=16, V2 / V1=17, V2 / V1=18, V2 / V1=19, V2 / V1=20, V2 / V1=21, V2 / V1=22, V2 / V1=23, and V2 / V1=24, or any one of the values satisfying the above range.
[0145] In some examples, the present application provides specific values of the closed pore volume, V1 is 0.04 cm 3 / g~0.16cm 3 / g.
[0146] In some embodiments, the present application further provides specific values of the closed pore volume, V1 is 0.05 cm 3 / g~0.15cm 3 / g.
[0147] This application selects the closed pore volume V1 as 0.04cm 3 / g~0.16cm 3 / g, which can occupy a certain pore volume, thereby limiting the amount of silicon material formed inside the porous carbon material, and can also buffer a part of the expansion deterioration of the silicon material caused by the expansion of the silicon material during the lithium insertion and extraction process.
[0148] In these examples, the closed pore volume V1 includes but is not limited to 0.04 cm 3 / g, 0.05cm 3 / g, 0.06cm 3 / g, 0.07cm 3 / g, 0.08cm 3 / g, 0.09cm 3 / g, 0.1cm 3 / g, 0.11cm 3 / g, 0.12cm 3 / g, 0.13cm 3 / g, 0.14cm 3 / g, 0.15cm 3 / g, 0.16cm 3 / g or any of the values satisfying the above ranges.
[0149] In some embodiments of the present application, the pore volume V2 of the through hole is 0.3 cm 3 / g~1.5cm 3 / g.
[0150] The pore volume of the through hole in this application affects the compressive strength of the silicon-carbon material, and also affects the amount of silicon material formed and the size of silicon grains. Therefore, the pore volume V2 of the through hole is selected as 0.3 cm in this application. 3 / g~1.5cm 3 / g.
[0151] In some embodiments of the present application, the pore volume V2 of the through hole is further 0.6 cm 3 / g~1.2cm 3 / g.
[0152] In these embodiments, the pore volume V2 of the through hole selected by the present application includes but is not limited to 0.3 cm 3 / g, 0.4cm 3 / g, 0.5cm3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g, 1.5cm 3 / g or any of the values satisfying the above ranges.
[0153] In some embodiments of the present application, the through pores include micropores, mesopores and macropores. Based on the total volume of the through pores, the volume ratio of the micropores, mesopores and macropores is (40% to 95%): (5% to 50%): (0 to 15%), preferably (45% to 95%): (5% to 45%): (0 to 10%).
[0154] The micropores, mesopores and macropores in this application include the conventional meanings in this field, such as the pore size of micropores is less than 2nm, mesopores are also called mesopores, and their pore size is 2nm to 50nm, and the pore size of macropores is greater than 50nm. This application includes the use of conventional testing instruments in this field to test the distribution of each pore, such as using the testing instrument ASAP2460-physical adsorption analyzer, placing the porous carbon material sample (porous carbon substrate) after drying and degassing treatment in liquid nitrogen, adjusting different test pressures, measuring the adsorption amount of nitrogen respectively, and drawing the adsorption and desorption isotherms. The shape of the pore is determined according to the shape of the hysteresis loop, the pore distribution is calculated according to different pore models, the BJH model is used to fit the pore size distribution curves of the mesopores and macropores, and the DFT model is used to fit the pore size distribution curve of the micropores.
[0155] In the present application, since the pore size affects the particle size and the amount of silicon material formed, the volume ratio between micropores, mesopores and macropores is selected as (40% to 95%): (5% to 50%): (0 to 15%). In these embodiments, the volume percentage of macropores includes but is not limited to any one of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15% or any one of the above range values. The present application also discloses that macropores are not included in some embodiments. The volume percentage of micropores includes but is not limited to any one of 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or any one of the above range values. The volume percentage of mesopores includes but is not limited to any one of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any one of the values satisfying the above range.
[0156] In some embodiments of the present application, the silicon-carbon material further comprises a silicon carbide material layer, the silicon carbide material layer is formed on at least a portion of the inner wall of the through hole, one side of the silicon carbide material layer is connected to the inner wall of the through hole, and the other side is connected to the nano silicon grains. In these embodiments, the thickness of the silicon carbide material layer is less than 0.7 nm. More preferably, it is less than 0.4 nm.
[0157] The formation of the silicon carbide material layer of the present application is affected by the preparation conditions. For example, during the growth of silicon grains, the silicon grains close to the inner wall of the through hole are easy to contact the wall and react to form a silicon carbide material layer. The hardness of the silicon carbide material layer is greater than that of the silicon material, and it can limit the degree of outward expansion when the silicon material expands. And the thickness of the silicon carbide material layer is not easy to be too thick, because the thickness of the silicon carbide material layer affects the conductivity of the silicon-carbon material. The thickness of the silicon carbide material layer in the present application is mainly obtained with the help of the relevant X-ray spectrum related to it.
[0158] The present application discloses in these embodiments that a silicon carbide material layer is formed on the interface of the inner wall of a portion of the through hole where the nano-silicon grains are in contact with the porous carbon material, the silicon carbide material layer is located between the through hole and the nano-silicon grains, one side of the silicon carbide material layer is connected to the inner wall of the through hole of the porous carbon material, and the other side is connected to the nano-silicon to form a silicon carbide interface layer, and the silicon carbide interface layer is arranged adjacent to the nano-silicon grains to limit the degree of outward expansion of the nano-silicon grains during lithium insertion and extraction.
[0159] The present application discloses in these embodiments that the silicon-carbon material further includes a carbon coating layer, and the carbon coating layer is disposed along the outer surface of the porous carbon material.
[0160] In addition, the carbon coating layer in the present application includes a carbon material layer arranged along the outer surface of the porous carbon material to form an outer shell layer that wraps the porous carbon material. On the one hand, the outer shell layer can reduce the probability of nano-silicon contacting with the outside air and then being oxidized, and on the other hand, it can reduce the probability of nano-silicon grains contacting and reacting with the electrolyte.
[0161] In some embodiments of the present application, the carbon coating layer is amorphous carbon, such as soft carbon or hard carbon obtained by cracking during the preparation process. The present application discloses in these embodiments that the thickness of the carbon coating layer is 5nm to 50nm, preferably 10nm to 30nm. The carbon coating layer of suitable thickness will not affect the embedding of lithium ions and the capacity of silicon-carbon materials, but can also effectively protect the internal silicon particles to reduce the probability of side reactions. The thickness of the carbon coating layer in the present application can also be obtained by means of the relevant X-ray spectrum related to it.
[0162] In some embodiments of the present application, the silicon-carbon material includes silicon element, and the mass percentage content of the silicon element is w based on the total mass of the silicon-carbon material. 硅 , satisfying: w硅 It is 38.0% to 48.0%.
[0163] In some embodiments of the present application, w 硅 It is 40.0% to 45.0%.
[0164] In some embodiments of the present application, the silicon-carbon material includes carbon element, and the mass percentage content of the carbon element is w based on the total mass of the silicon-carbon material. 碳 , satisfying: w 碳 It is 50.0% to 55.0%.
[0165] In this application, the amount of silicon material formed in the through hole affects the probability of its reaction with the electrolyte. Generally speaking, the more the amount is formed, the greater its expansion in the lithium insertion and extraction cycle, and the greater the probability of reacting with the electrolyte. The content of silicon material also affects the capacity of the battery. Limited by the pore volume of the through hole and the pore volume of the closed hole, this application chooses to control w 硅 In these embodiments, w 硅 Including but not limited to any one of 38.0%, 40.0%, 42.0%, 43.0%, 44.0%, 45.0%, 48.0% or any one of the above range values. The silicon-carbon material in this application mainly comprises silicon and carbon. In addition, it also comprises other elements that are not necessary or indispensable in porous carbon materials. The silicon content and the carbon content can be measured with the help of relevant standards. For example, the silicon content can refer to GB / T 20975.5-2020, and the carbon content can refer to GB / T 20123-2006 / ISO 15350:2000.
[0166] In some embodiments of the present application, the porous carbon material comprises porous carbon material particles, and the particle size of the porous carbon material particles meets the following requirements: Dv50 is 3.0 μm to 6.5 μm; Dv90 is 13.5 μm to 18.5 μm; and Dv10 is 0.9 μm to 2.5 μm.
[0167] In some embodiments, the present application discloses that the particle size of the porous carbon material particles meets the following requirements: Dv50 is 3.5 μm to 6.0 μm; Dv90 is 14.0 μm to 18.0 μm; and Dv10 is 1.0 μm to 2.0 μm.
[0168] Dv90 in this application includes 90% of the volume of particles with a diameter smaller than it, Dv10 includes 10% of the volume of particles with a diameter smaller than it, Dv50 includes 50% of the volume of particles with a diameter larger than it, and 50% of the volume of particles smaller than it, which is also called the median diameter, and is usually used to indicate the average particle size of the particles. Whether it is Dv90, Dv10 or Dv50, conventional measurement methods in the art can be used, such as using a particle size analyzer to measure the particle size distribution and then obtain it by statistics. In these embodiments, this application chooses to refer to the laser diffraction particle size analysis method for determination, specifically referring to the standard GB / T19077-2016 to obtain a particle size distribution diagram, and then obtains it by calculation.
[0169] The present application controls the particle size of the porous carbon material particles to meet the following requirements: Dv50 is 3.0 μm to 6.5 μm; Dv90 is 13.5 μm to 18.5 μm; and Dv10 is 0.9 μm to 2.5 μm. This allows the nano-silicon grains to be efficiently formed in the through holes of the porous carbon material. The present application discloses in these embodiments that Dv50 is any one of 3.0 μm, 3.3 μm, 3.5 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5.0 μm, 5.2 μm, 5.5 μm, 5.8 μm, 6.0 μm, and 6.5 μm, or any one of the values that meet the range. Dv90 includes but is not limited to any one of 13.5μm, 14.0μm, 14.5μm, 15.0μm, 15.5μm, 16.0μm, 16.5μm, 17.0μm, 17.5μm, 18.0μm, 18.5μm or any one of the above range values. Dv10 includes but is not limited to any one of 0.9μm, 1.0μm, 1.2μm, 1.5μm, 1.8μm, 2.0μm, 2.2μm, 2.5μm or any one of the above range values.
[0170] The present application discloses in some embodiments that the specific surface area of the porous carbon material particles is 900 m 2 / g~1550m 2 / g.
[0171] The present application discloses in some embodiments that the specific surface area of the porous carbon material particles is 1000 m 2 / g~1500m 2 / g.
[0172] The specific surface area in this application includes any conventional concept in the art, which can be obtained by testing using instruments or methods known in the art, such as testing the specific surface area using a gas adsorption method, specifically referring to the standard test of GB / T19587-2017.
[0173] In these embodiments, the specific surface area of the porous carbon material particles is controlled to be 900 m 2 / g~1550m 2 / g, so as to facilitate the efficient formation of nano-silicon grains in the through holes of the porous carbon material. The present application also discloses in these embodiments that the specific surface area of the porous carbon material particles includes but is not limited to 900m 2 / g, 990m 2 / g、1000m 2 / g, 1050m 2 / g、1100m 2 / g, 1150m 2 / g、1200m 2 / g, 1250m 2 / g、1300m 2 / g, 1350m 2 / g、1400m 2 / g, 1450m 2 / g、1500m 2 / g, 1550m 2 / g or any of the values satisfying the above ranges.
[0174] The present application discloses in some embodiments that the tap density of the porous carbon material particles is 0.22 g / cm 3 ~0.48g / cm 3 .
[0175] The present application discloses in some embodiments that the tap density of the porous carbon material particles is 0.25 g / cm 3 ~0.45g / cm 3 .
[0176] The tap density in this application includes any common concept in the art, which can be obtained by testing using instruments or methods known in the art, such as by testing with reference to standard GB / T5162-2006. In these embodiments, the tap density of the porous carbon material particles is controlled to be 0.22 g / cm 3 ~0.48g / cm 3 Under the premise of ensuring that the porous carbon material has the above-mentioned particle size and specific surface area, nano-silicon grains are effectively formed.
[0177] The present application discloses in these embodiments that the tap density of the porous carbon material particles includes but is not limited to 0.22 g / cm 3 , 0.25g / cm 3 , 0.30g / cm 3 , 0.35g / cm 3 , 0.40g / cm 3, 0.45g / cm 3 , 0.48g / cm 3 Any one of or any one of the above range values.
[0178] The present application discloses in some embodiments that the compacted density of 5 tons of porous carbon material particles is 0.45 g / cm 3 ~0.80g / cm 3 .
[0179] The present application discloses in some embodiments that the compacted density of 5 tons of porous carbon material particles is 0.50 g / cm 3 ~0.75g / cm 3 .
[0180] The compaction density in this application includes any conventional concept in the art, which can be obtained by testing using instruments or methods known in the art, such as limiting the pressure of cold pressing to 5 tons, and obtaining it by referring to the calculation method of GB / T 24533-2009. For example, it is measured using an electronic pressure tester (such as UTM7305). Specifically, a specific amount M of the powder sample to be tested is placed on a special pressing die (with a bottom area of S0) and different pressures are set. Each pressure is maintained for 30 seconds and then released. After 10 seconds, the thickness H0 of the powder pressed under the pressure is read on the device. The compaction density under the pressure is obtained by calculation, and the compaction density of the negative plate material under the pressure is equal to M / (H0×S0).
[0181] The present application selects to control the compaction density of the porous carbon material particles to be 0.50 g / cm when the cold pressing pressure is 5 tons. 3 ~0.75g / cm 3 , so as to effectively form nano-silicon grains while ensuring that the porous carbon material has the above-mentioned particle size, specific surface area, and tap density.
[0182] The present application discloses in these examples that the compacted density of the porous carbon material particles at 5 tons includes but is not limited to 0.45 g / cm 3 , 0.50g / cm 3 , 0.55g / cm 3 , 0.60g / cm 3 , 0.65g / cm 3 、0.70g / cm 3 , 0.75g / cm 3 、0.80g / cm 3 Any one of or any one of the above range values.
[0183] In some embodiments of the present application, the particle size of the silicon-carbon composite particles satisfies: (Dv90-Dv10) / Dv50 is 1.2 to 2.8.
[0184] In some embodiments of the present application, the particle size of the silicon-carbon composite particles satisfies: (Dv90-Dv10) / Dv50 is 1.3 to 2.5.
[0185] Dv90 in this application includes 90% of the volume of particles with a diameter smaller than it, Dv10 includes 10% of the volume of particles with a diameter smaller than it, Dv50 includes 50% of the volume of particles with a diameter larger than it, and 50% of the volume of particles smaller than it, which is also called the median diameter, and is usually used to indicate the average particle size of the particles. Whether it is Dv90, Dv10 or Dv50, conventional measurement methods in the art can be used, such as using a particle size analyzer to measure the particle size distribution and then obtain it by statistics. In these embodiments, this application chooses to refer to the laser diffraction particle size analysis method for determination, specifically referring to the standard GB / T19077-2016 to obtain a particle size distribution diagram, and then obtains it by calculation.
[0186] The particle size of the silicon-carbon composite particles selected in the present application satisfies: (Dv90-Dv10) / Dv50 is 1.2 to 2.8, so that the silicon-carbon composite particles of large and small particle sizes are properly matched to improve the volume energy density of the battery while minimizing the expansion of the silicon-carbon material during the lithium insertion and extraction process.
[0187] In these embodiments, the present application provides (Dv90-Dv10) / Dv50 including but not limited to any one of 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8 or any one of the values satisfying this range.
[0188] Some embodiments of the present application set specific numerical limits on the particle sizes of the silicon-carbon composite particles, such as Dv50 of 3.5 μm to 9.0 μm, Dv90 of 14.0 μm to 21.0 μm, and Dv10 of 0.9 μm to 3.0 μm.
[0189] In some embodiments of the present application, Dv50 is given as 4.0 μm to 6.5 μm; Dv90 is given as 15.0 μm to 20.0 μm; and Dv10 is given as 1.0 μm to 2.5 μm.
[0190] In this application, since the size of silicon grains will affect the diffusion path of lithium ions, this application controls the silicon-carbon composite particles to have a suitable particle size under the premise that the average particle size of the above-mentioned silicon grains is ≥5nm to balance the overall performance of the silicon-carbon material. In these embodiments, the present application discloses that the Dv50 of the silicon-carbon composite particles is 3.5μm, 3.8μm, 4.0μm, 4.2μm, 4.5μm, 5.0μm, 5.5μm, 5.8μm, 6.0μm, 6.2μm, 6.5μm, 6.7μm, 7.0μm, 7.5μm, 8.0μm, 8.5μm, 9.0μm, or any one of the above-mentioned range values. The present application also discloses in these embodiments that the Dv90 of the silicon-carbon composite particles is 14.0 μm, 14.5 μm, 15.0 μm, 15.2 μm, 15.5 μm, 15.8 μm, 16.0 μm, 16.5 μm, 17.0 μm, 17.5 μm, 18.0 μm, 18.5 μm, 19.0 μm, 19.5 μm, 20.0 μm, 20.5 μm, 21 μm, or any one of the above range values. The present application also provides in these embodiments that the Dv10 is 0.9 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3.0 μm, or any one of the above range values.
[0191] In some embodiments of the present application, the specific surface area of the silicon-carbon composite particles is 3.0 m 2 / g~12.0m 2 / g.
[0192] In some embodiments of the present application, the specific surface area of the silicon-carbon composite particles is 5.0 m 2 / g~10.0m 2 / g.
[0193] The specific surface area in this application includes any conventional concept in the art, which can be obtained by testing using instruments or methods known in the art, such as testing the specific surface area using a gas adsorption method, specifically referring to the standard test of GB / T19587-2017.
[0194] The present invention selects silicon-carbon composite particles with a specific surface area of 3.0 m 2 / g~12.0m 2 / g, so that the silicon-carbon material has suitable lithium insertion and extraction sites to improve the capacity and cyclability of the battery.
[0195] In some embodiments of the present application, the tap density of the silicon-carbon composite particles is 0.5 g / cm 3 ~1.0g / cm 3 .
[0196] In some embodiments of the present application, the tap density of the silicon-carbon composite particles is 0.6 g / cm 3 ~0.8g / cm 3 .
[0197] The tap density in the present application includes any conventional concept in the art, which can be obtained by testing using instruments or methods known in the art, such as by testing with reference to standard GB / T5162-2006.
[0198] The tap density of the silicon-carbon composite particles selected in this application is 0.5 g / cm 3 ~1.0g / cm 3 , while ensuring that the silicon-carbon composite particles have the above-mentioned particle size and specific surface area, the volume energy density of the battery can be effectively improved.
[0199] The present application discloses in these embodiments that the tap density of the silicon-carbon composite particles includes but is not limited to 0.5 g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 Any one of or any one of the above range values.
[0200] In some embodiments of the present application, the compacted density of 5 tons of silicon-carbon composite particles is 0.80 g / cm 3 ~1.1g / cm 3 .
[0201] In some embodiments of the present application, the compacted density of 5 tons of silicon-carbon composite particles is 0.90 g / cm 3 ~1.05g / cm 3 .
[0202] The compaction density in this application includes any conventional concept in the art, which can be obtained by testing using instruments or methods known in the art, such as limiting the pressure of cold pressing to 5 tons, and obtaining it by referring to the calculation method of GB / T 24533-2009. For example, it is measured using an electronic pressure tester (such as UTM7305). Specifically, a specific amount M of the powder sample to be tested is placed on a special pressing die (with a bottom area of S0) and different pressures are set. Each pressure is maintained for 30 seconds and then released. After 10 seconds, the thickness H0 of the powder pressed under the pressure is read on the device. The compaction density under the pressure is obtained by calculation, and the compaction density of the negative plate material under the pressure is equal to M / (H0×S0).
[0203] The compaction density of 5 tons of silicon-carbon composite particles selected in this application is 0.80 g / cm 3 ~1.1g / cm 3 To effectively improve the capacity of the battery and enhance its practicality.
[0204] The present application discloses in these examples that the compacted density of the silicon-carbon composite particles at 5 tons is 0.80 g / cm 3 , 0.90g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 Any one of or any one of the above range values.
[0205] In some embodiments of the present application, the powder resistivity of the silicon-carbon composite particles at 4 MPa is 1.30 Ω·cm to 3.80 Ω·cm.
[0206] The powder resistivity of the silicon-carbon composite particles in this application is different from the resistivity of the electrode, which is used to characterize the conductivity of the silicon-carbon material itself. The powder resistivity in this application includes any conventional concept in the art, such as placing an appropriate amount of silicon-carbon material in the feeding cup of a resistivity tester, applying pressure, manually collecting data, recording the powder resistivity test results at different pressure points and then taking the average value, and the test pressure is 4MPa.
[0207] The powder resistivity of the silicon-carbon composite particles of the present application at 4Mpa is 1.30Ω·cm to 3.80Ω·cm. This shows that the amount of silicon grains formed in the silicon material particles of the present application is appropriate and effective, because in the silicon-carbon material, the porous carbon material has good conductivity, while the conductivity of the silicon material is weak. The powder resistivity of the carbon composite particles selected by the present application at 4Mpa is 1.30Ω·cm to 3.80Ω·cm, which is conducive to improving the capacity and cyclability of the battery.
[0208] In some embodiments of the present application, the lithium removal capacity of the silicon-carbon composite particles is 1300mAh / g to 1500mAh / g, and the first coulomb efficiency is 77% to 81%. In these embodiments, the silicon-carbon composite particles are used as the positive electrode active material, the metal lithium sheet is used as the counter electrode, and a CR2430 button battery is assembled. At 25°C, the charge and discharge voltage is 0.005 to 2.0V, and the lithium removal capacity is measured to be 1300mAh / g to 1500mAh / g, and the first coulomb efficiency is 77% to 81%. The lithium removal capacity obtained by the present application is 1300mAh / g to 1500mAh / g, which matches the silicon content in the silicon-carbon material and the positional relationship of the silicon material.
[0209] In some embodiments of the present application, in the dQ / dV curve of the silicon-carbon composite particles, I1 is a peak intensity near 0.3V~0.35V; I2 is a peak intensity near 0.43V~0.50V; it satisfies: I1 / I2=1.4~1.8; the dQ / dV curve of the silicon-carbon composite particles includes silicon-carbon composite particles as the positive electrode active material, a metal lithium sheet as the counter electrode, assembled to form a CR2430 button battery, at 25°C, the charge and discharge voltage is 0.005V~2.0V, and the charge and discharge capacity and the working electrode potential are obtained by differential processing.
[0210] The differential capacity / voltage curve of the charge and discharge curve of the silicon-carbon material provided in the present application under certain conditions gives a peak with a certain intensity at a certain voltage, and the ratio between the peaks is used to indicate that the amount of silicon material particles formed in the through-holes is appropriate, and the appropriate formation amount is beneficial to improving the cyclability of the battery.
[0211] In summary, the present application provides a silicon-carbon material, which comprises a silicon-carbon composite particle with a certain particle size, specific surface area, tap density and compacted density, the silicon-carbon composite particle comprises a porous carbon material with a certain pore size, the porous carbon material comprises a certain number of through holes with a pore volume, the silicon-carbon composite particle also comprises a certain number of closed holes with a pore volume, nano-silicon grains are distributed along the inner wall of the through hole of the porous carbon material and form a suitable particle size, the nano-silicon grains with a suitable particle size are further stacked along the inner wall of the through hole to form a layered or sheet-like film, and the layered or sheet-like film directly contacts the inner wall of the through hole to generate a silicon carbide material layer. This arrangement can not only reduce the probability of its reaction with the electrolyte, but also control the expansion rate of the silicon material, because the expansion of the silicon material is not only limited by the through hole, but also by the silicon carbide material layer. In addition, a carbon coating layer is formed on the outside of the porous carbon material, which can reduce the probability of the nano-silicon grains being in contact with the outside air and then being oxidized, and can reduce the probability of the nano-silicon grains being in contact with the electrolyte. Therefore, the silicon-carbon material provided by this application reduces the probability of side reactions between the silicon material and the electrolyte under the premise of controlling the expansion degree of the silicon material during the process of lithium ion extraction, thereby improving the cyclability of the battery to a certain extent.
[0212] In order to better explain the structure and properties of the above silicon-carbon material, a detailed description is given below in conjunction with its preparation method.
[0213] Preparation method of silicon carbon material
[0214] The present application provides, in some embodiments, a method for preparing a silicon-carbon material, including the following preparation process:
[0215] providing a porous carbon substrate;
[0216] A silicon source is introduced into the porous carbon substrate to generate a porous carbon material comprising nano-silicon grains and a silicon carbide material layer;
[0217] A carbon source is introduced into a porous carbon material comprising nano-silicon grains and a silicon carbide material layer to generate a silicon-carbon negative electrode material comprising a carbon coating layer.
[0218] In some embodiments of the present application, the porous carbon substrate comprises carbon, oxygen and nitrogen, and the mass ratio of carbon to oxygen and nitrogen is (94% to 97%): (2% to 4%): (1% to 2%);
[0219] Preferably, the ash content of the porous carbon substrate is ≤ 0.5%.
[0220] The porous carbon substrate of the present application is made from conventional carbon material precursors in the art. The types of carbon material precursors are not particularly limited and may include, but are not limited to, asphalt-based carbon material precursors, asphaltene-based carbon material precursors, coal-based carbon material precursors, coke-based carbon material precursors, biochar-based carbon material precursors, carbon black-based carbon material precursors, oil product-based carbon material precursors, tar-based carbon material precursors, polymer-based carbon material precursors, protein-based carbon material precursors, carbohydrate-based carbon material precursors, cotton-based carbon material precursors, fat-based carbon material precursors, waste-based carbon material precursors, graphite-based carbon material precursors, melamine-based carbon material precursors, wood-based carbon material precursors, porous graphene, porous graphene oxide, activated carbon and combinations thereof. Carbon material precursors of this type are easy to prepare porous carbon materials that meet the above-mentioned particle size, specific surface area, tap density and compacted density. The present application discloses a method for preparing a porous carbon substrate in these embodiments, such as high-temperature sintering of a carbon material precursor to remove impurities, and then forming pores to obtain a porous carbon material. The pore forming of the present application includes chemical methods such as strong alkali corrosion. The measurement method of carbon elements, oxygen elements and nitrogen elements in the porous carbon substrate of the present application includes any conventional method in the art, such as measured according to relevant test standards. The present application discloses in these embodiments that the mass percentage of carbon elements in the porous carbon substrate includes any one of 94%, 95%, 96%, 97% or any one of the above range values. The mass percentage of oxygen elements in the porous carbon substrate includes any one of 2%, 3%, 4% or any one of the above range values. The mass percentage of nitrogen elements in the porous carbon substrate includes any one of 1%, 2% or any one of the above range values.
[0221] The ash content in the present application includes inorganic matter remaining after the porous carbon substrate is calcined at high temperature. The measurement method of the ash content can refer to GB / T 1429-2009.
[0222] In some embodiments of the present application, the reaction conditions for generating a porous carbon material including nano-silicon grains and a silicon carbide material layer include one or more of the following:
[0223] (5.1) The reaction temperature is 500°C to 700°C, and the silicon source is introduced for 3h to 42h; preferably, the reaction temperature is 650°C to 700°C; preferably, the silicon source is introduced for 5h to 40h;
[0224] (5.2) The silicon source comprises a silicon source gas and a diluent gas, wherein the volume percentage of the silicon source gas is 15% to 95%; preferably, the volume percentage of the silicon source gas is 20% to 50%; preferably, the silicon source gas comprises any one or two of monosilane and disilane;
[0225] (5.3) The ventilation volume of the silicon source is 0.3L / min~1.4L / min.
[0226] The present application discloses in some embodiments that the reaction temperature for generating a porous carbon material comprising nano-silicon grains and a silicon carbide material layer comprises any one of 500°C, 600°C, 650°C, 680°C, and 700°C, or satisfies any one of the above ranges. The present application discloses in these embodiments that the time for introducing a silicon source comprises any one of 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, 37h, 38h, 39h, 40h, 41h, and 42h, or satisfies any one of the above ranges. In these embodiments, the present application selects a reaction temperature of 500°C to 700°C and a silicon source introduction time of 3h to 42h; this facilitates the growth of silicon grains with a grain size d1 ≥ 5nm in the through holes, and the silicon grains are stacked along the inner wall of the through holes to form a layered or sheet-like film. During the continuous growth process, the layered or sheet-like film is also easy to generate a silicon carbide material layer in the area that is in direct contact with the inner wall of the through hole within the above-mentioned reaction temperature, and the silicon carbide material layer and the through holes of the porous carbon material limit the growth of the silicon grains, and finally generate nano-silicon grains with a certain suitable particle size.
[0227] The present application discloses in some embodiments that the silicon source for forming silicon grains includes a silicon source gas and a dilution gas, wherein the silicon source gas includes but is not limited to monosilane, disilane, etc., and the dilution gas includes an inert gas, and the inert gas includes conventional inert gases in the art, including but not limited to rare gases corresponding to group zero in the periodic table, etc. The present application discloses in these embodiments that the volume fraction of the silicon source gas in the silicon source includes any one of 15%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, or any one of the values in the above ranges.
[0228] The present application discloses in some embodiments that it is also necessary to control the ventilation volume of the silicon source during the generation of a porous carbon material comprising nano-silicon grains and a silicon carbide material layer. The ventilation volume of the silicon source can be measured using conventional measurement methods in the art, such as by setting a flow valve in a reaction device. The present application discloses in these embodiments that the ventilation volume of the silicon source includes any one of 0.3L / min, 0.4L / min, 0.5L / min, 0.6L / min, 0.7L / min, 0.8L / min, 0.9L / min, 1.0L / min, 1.1L / min, 1.2L / min, 1.3L / min, 1.4L / min or any one of the above range values. The present application controls the volume percentage and ventilation volume of each component in the silicon source to control the growth rate of silicon grains, thereby affecting the grain size of silicon grains and the formation and thickness of the silicon carbide material layer.
[0229] In some embodiments of the present application, the reaction conditions for generating a silicon-carbon negative electrode material including a carbon coating layer include the following:
[0230] (6.1) The reaction temperature is 600°C to 750°C, and the time for introducing the carbon source is 0.5h to 5h. The preferred reaction temperature is 650°C to 700°C; the preferred time for introducing the carbon source is 1h to 4h.
[0231] (6.2) The carbon source comprises a carbon source gas and a diluent gas, wherein the volume fraction of the carbon source gas is 15% to 95%; preferably, the volume fraction of the carbon source gas is 20% to 40%; preferably, the carbon source gas comprises any one of methane, ethylene, acetylene, and propylene, or a combination of two or more thereof;
[0232] (6.3) The aeration rate of the carbon source is 1.0 L / min to 3.0 L / min, preferably 1.5 L / min to 2.5 L / min.
[0233] The reaction temperature of the carbon coating layer of the present application includes any one of 600°C, 650°C, 700°C, 750°C or any one of the above range values. The time for introducing the carbon source in the present application includes any one of 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or any one of the above range values. At the reaction temperature of the present application and the time for introducing the carbon source, the carbon coating layer is formed along the outer surface of the porous carbon material and has a certain thickness. And under this reaction condition, the silicon material with a layered or sheet-like film stacked along the inner wall of the through hole may continue to generate a silicon carbide material layer in the area directly in contact with the inner wall of the through hole.
[0234] The present application discloses in some embodiments that the carbon source for forming the carbon coating layer includes a carbon source gas and a dilution gas. As described above, the dilution gas includes an inert gas, and the inert gas includes an inert gas conventional in the art, including but not limited to the rare gas corresponding to the zero group in the periodic table. The carbon source gas includes but is not limited to methane, ethylene, acetylene, propylene, etc. The present application also discloses in these embodiments that the volume percentage of the carbon source gas includes but is not limited to 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or any one of the above range values. The ventilation volume of the carbon source includes but is not limited to any one of 1.0L / min, 2.0L / min, 3.0L / min or any one of the above range values. The present application generates a carbon coating layer with a thickness of 5nm to 50nm and a silicon carbide material layer with a thickness of less than 0.7nm under the reaction condition control of the volume percentage of the carbon source gas and the ventilation amount of the carbon source.
[0235] Negative electrode
[0236] In some embodiments of the present application, a negative electrode sheet is disclosed, which includes a negative electrode current collector and a negative electrode film layer located on at least one side of the negative electrode current collector, and the negative electrode film layer includes a silicon-carbon material as a negative electrode active material, and also includes other negative electrode active materials, such as carbonaceous materials, specifically including but not limited to one or a combination of two or more of artificial graphite, natural graphite, soft carbon, and hard carbon. Among them, artificial graphite, natural graphite, soft carbon, hard carbon, etc. include any form of materials conventional in the art, and include any conventional manufacturers and models in the art.
[0237] In some embodiments of the present application, it is disclosed that the negative electrode film layer also includes a conductive agent, a thickener, a binder, etc., wherein the conductive agent includes but is not limited to one or a combination of two of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers; the thickener includes cellulose and its sodium salt, and cellulose includes methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, etc.; the binder includes but is not limited to polyvinyl alcohol, polyethylene glycol, sodium carboxymethyl cellulose, polyethylene oxide, polyacrylic acid, polyacrylamide, sodium alginate, styrene-butadiene rubber (SBR), etc.
[0238] The negative electrode current collector of the present application may be a metal foil or a composite current collector, the metal foil may be a copper foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and the like.
[0239] In some embodiments, the present application discloses the mass ratios of silicon-carbon material, carbonaceous material, conductive agent, thickener and binder in the negative electrode film layer: (10% to 50%): (45% to 95%): (0.2% to 2.0%): (0.2% to 2.0%): (1.2% to 2.2%).
[0240] Positive electrode
[0241] In some embodiments of the present application, a positive electrode sheet is disclosed, which includes a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector. The positive electrode film layer in the present application includes positive electrode active particles, a positive electrode conductive agent, a positive electrode binder, etc. The present application does not specifically limit the specific types of positive electrode active particles. For example, when the positive electrode sheet is applied to a lithium-ion battery, the positive electrode active particles include but are not limited to LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM111), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 CO 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 CO 0.1 Mn 0.1O2(NCM811), LiNi 0.85 CO 0.15 Al 0.05 One or more of O2, LiFePO4 (LFP) and LiMnPO4.
[0242] For example, when the positive electrode is used in a sodium ion battery, the positive electrode active particles include but are not limited to at least one of sodium transition metal oxides, polyanionic compounds, and Prussian blue compounds. Among them, in the sodium transition metal oxide, the transition metal can be one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1. Polyanionic compounds include sodium vanadium trifluorophosphate (Na3V2(PO4)2F3), sodium vanadium fluorophosphate (NaVPO4F), sodium vanadium phosphate (Na3V2(PO4)3), Na4Fe3(PO4)2P2O7, NaFePO4, etc. Prussian blue compounds are Na x M1M2(CN)6, wherein M1 and M2 are one or more of Fe, Mn, Co, Ni, Cu, Zn, Cr, Ti, V, Zr, and Ce, and 0<x≤2.
[0243] The positive electrode conductive agent includes but is not limited to one or more combinations of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers. The positive electrode binder includes but is not limited to one or more combinations of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylate resin, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, carboxymethyl chitosan, etc.
[0244] The positive electrode current collector in the present application may be a metal foil or a composite current collector, wherein the metal foil may be an aluminum foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0245] Electrolyte
[0246] In some embodiments of the present application, an electrolyte is disclosed, which includes a sodium salt or a lithium salt and an organic solvent, and the organic solvent can be an organic solvent commonly used in the art for electrolytes. As an example, the organic solvent can be selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) at least one or two combinations. The sodium salt or lithium salt may be a sodium salt or lithium salt commonly used in the art for electrolyte, such as sodium hexafluorophosphate, lithium hexafluorophosphate, and the like.
[0247] Isolation film
[0248] According to some embodiments of the present application, the battery not only includes a negative electrode sheet, a positive electrode sheet and an electrolyte, but also includes a separator stacked together. The stacking method includes but is not limited to the conventional winding or stacking in the art. The material, size, etc. of the separator include but are not limited to any conventional form in the art. Similarly, the material, size, etc. of the positive electrode sheet include but are not limited to any conventional form in the art. For example, the separator is arranged between the positive electrode sheet and the negative electrode sheet to play an isolating role. The separator includes a substrate and also includes a functional coating provided on at least one surface of the substrate. The functional coating can be used to improve the heat resistance, mechanical strength, etc. of the separator. For example, the functional coating may also include other functional materials (such as ceramic particles, other polymers, etc.). Ceramic particles include but are not limited to boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, etc.; the present application has no particular restrictions on the type of the separator substrate, and any known substrate that can be used for the secondary battery separator can be selected. In some embodiments, the separator substrate includes but is not limited to a single-layer film or a multi-layer composite film of one or more of glass fiber, non-woven fabric, polyethylene, and polypropylene.
[0249] [Preparation of silicon-carbon materials]
[0250] The present application discloses in some embodiments a method for preparing a silicon-carbon material, comprising the following preparation steps:
[0251] S1. Providing a porous carbon substrate, wherein the porous carbon substrate comprises carbon, oxygen and nitrogen, wherein the mass ratio of carbon to oxygen and nitrogen is (94% to 97%): (2% to 4%): (1% to 2%), and the ash content of the porous carbon substrate is ≤0.5%;
[0252] At the same time, the porous carbon substrate comprises porous carbon material particles, and the pore volume, average pore diameter, number and distribution of through holes, particle size, specific surface area and tap density of the porous carbon material particles meet the following requirements:
[0253] a. The average pore size is 1.0nm to 5.0nm;
[0254] b. The volume percentage of macropores is ≤15%, and the volume ratio of micropores to hollows is (40-95%):(5-50%);
[0255] c. Dv50 is 3.0μm to 6.5μm; Dv90 is 13.5μm to 18.5μm; Dv10 is 0.9μm to 2.5μm;
[0256] d. Specific surface area is 900m 2 / g~1550m 2 / g;
[0257] e. Tap density is 0.22g / cm 3 ~0.48g / cm 3 ;
[0258] f. Compacted density is 0.45g / cm 3 ~0.80g / cm 3 ;
[0259] S2, placing the porous carbon substrate of S1 in a CVI device, introducing a silicon source for 3h to 42h, and performing a chemical vapor deposition reaction at 500°C to 700°C to generate a porous carbon material containing nano-silicon grains, wherein the CVI device comprises a fluidized bed and any one of a rotary kiln, a push plate furnace or a tubular furnace; the ventilation volume of the silicon source is 0.2L / min to 1.5L / min, the silicon source comprises a silicon source gas and a dilution gas, and the volume fraction of the silicon source gas is 15% to 95%; the silicon source gas comprises any one or two of monosilane and disilane;
[0260] S3. A carbon source is introduced into the porous carbon material containing nano-silicon grains in S2 for 0.5 h to 5 h, and a reaction is carried out at 600°C to 750°C to obtain a silicon-carbon negative electrode material containing a carbon coating layer. The carbon source has a ventilation rate of 1.0 L / min to 3.0 L / min, and the carbon source contains a carbon source gas and a dilution gas. The volume fraction of the carbon source gas is 15% to 95%; the carbon source gas contains any one of methane, ethylene, acetylene, and propylene, or a combination of two or more thereof.
[0261] Among them, Examples 1 to 16 are silicon-carbon materials obtained according to the raw materials listed in Tables 1, 2, and 3 and the process parameters listed in Table 4, and the particle size, specific surface area, etc. of the silicon-carbon materials are shown in Table 5.
[0262] in, Figure 5 This is the electron microscope image of the silicon-carbon material obtained in Example 8, which was tested using a field emission scanning electron microscope (Zeiss Gemini360) in accordance with the JY / T010-1996 standard. Figure 5 It can be seen that the silicon-carbon material is composed of irregular morphology particles with different particle sizes.
[0263] Figure 6 This is a schematic diagram of the structure of the silicon-carbon composite particles of this application, combined with Figure 6 It can be seen that the silicon-carbon composite particles 1 include a porous carbon material 1a, which has through holes, and nano-silicon grains 1b are distributed along the inner wall of the through holes of the porous carbon material 1a, and some remaining closed holes 1c are left; a silicon carbide material layer 1d is formed inside the through holes, and one side of the silicon carbide material layer 1d is connected to the inner wall of the through hole, and the other side is connected to the nano-silicon grains 1b. The remaining closed holes 1c formed on the inner wall of the through hole in the present application can be used to alleviate the partial expansion of the nano-silicon material when lithium is inserted, thereby alleviating the expansion of the silicon-carbon composite particles. The silicon carbide material layer can be used to limit the degree of outward expansion of the nano-silicon particles during the process of lithium insertion and extraction to reduce the effect of the reaction between the nano-silicon particles and the electrolyte.
[0264] Further integration Figure 7 It can be seen that a certain amount of silicon carbide material layer is indeed formed inside the silicon-carbon material. Figure 7 This is an X-ray photoelectron spectroscopy analysis spectrum of the silicon-carbon material obtained in Example 8. The thickness of the silicon carbide material layer is calculated to be less than 0.7 nm.
[0265] Figure 8 In order to enlarge the silicon-carbon material obtained in Example 8 to obtain the electron microscope image of the nano-silicon grain 1b, combined with Figure 8 It can be seen that the nano-silicon grains are stacked along the inner wall of the through hole to form a layered or sheet-like film.
[0266] Fig. 9 The transmission electron microscope image of the silicon-carbon material obtained in Example 8 is shown in FIG. Fig. 9 It can be seen that a carbon coating layer is formed on the outer surface of the porous carbon material, and the thickness of the carbon coating layer is 18.4 nm.
[0267] Fig.10 The X-ray diffraction pattern of the silicon-carbon material obtained in Example 8 can be obtained by using an X-ray diffractometer in a method known in the art. As an example, the XRD test general rules JIS K0131-1996 are specifically referred to, including the following requirements: (1) the sample is dry; (2) the sample particle size is less than 10 μm. If it is a pole piece scraping powder or a block sample, it needs to be ground and passed through a 200 mesh sieve. Fig.10 It can be seen that the silicon-carbon material has a strong silicon crystallization peak, and the silicon grain size of the silicon-carbon material calculated by the Scherrer formula is 7.2 nm.
[0268] Fig.11 The dQ / dV curve of the discharge curve of the silicon-carbon material obtained in Example 8 is shown in FIG. Fig.11 It can be seen that the silicon-carbon material I1 / I2=1.45, indicating that the amount of silicon material particles formed in the through-holes is appropriate, and the appropriate amount of formation is conducive to improving the cyclability of the battery. Among them, I1 is the peak intensity near 0.3V~0.35V; I2 is the peak intensity near 0.43V~0.50V.
[0269] Comparative Example 1
[0270] A silicon-carbon material is provided. The carbon substrate used to generate the silicon-carbon material is different from that of the present application. The silicon grains are generated at a low temperature of 450°C. The average particle size of the obtained nano-silicon grains is smaller than the average pore size of the porous carbon material, and no silicon carbide material layer is generated. See Tables 1 to 5 for details.
[0271] Comparative Example 2
[0272] A silicon-carbon material is provided. The carbon substrate for generating the silicon-carbon material remains the same as that of the present application. A low temperature of 450°C is used in the process of generating silicon grains, and a reaction temperature of 500°C is used in the carbon coating process, resulting in no generation of a silicon carbide material layer. See Tables 1 to 5 for details.
[0273] Among them, the transmission electron microscope images and X-ray photoelectron spectroscopy analysis patterns of the silicon-carbon materials obtained in Comparative Examples 1 and 2 were obtained, and it was analyzed that no silicon carbide material layer was actually generated.
[0274] [Performance test of silicon carbon materials]
[0275] ①Particle size test:
[0276] Refer to the standard GB / T19077-2016: obtain the volume particle size distribution curve of porous carbon particles or silicon-carbon composite particles, take the particle size corresponding to 50% of the cumulative volume distribution percentage as the average particle size Dv50, take the particle size corresponding to 90% of the cumulative volume distribution percentage as the average particle size Dv90, take the particle size corresponding to 10% of the cumulative volume distribution percentage as the average particle size Dv10. The test instrument can be the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.
[0277] ②Specific surface area test:
[0278] Referring to the standard GB / T19587-2017: The porous carbon particles or silicon-carbon composite particles are tested by nitrogen adsorption specific surface area analysis test method, and the specific surface area is calculated by BET (Brunauer Emmett Teller) method. The test instrument can be TRISTAR II 3020 specific surface area and porosity analyzer of Micromeritics, USA.
[0279] ③Through hole volume test:
[0280] The porous carbon particles obtained are tested according to the GB / T21650.2-2008 test method. The test instrument can be a TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, USA.
[0281] ④Pore volume test of closed pores:
[0282] Refer to GB / T24586-2009 to obtain the test true density of silicon-carbon materials, refer to GB / T 20975.5-2020 to obtain the silicon content in silicon-carbon materials, and refer to GB / T 20123-2006 / ISO 15350:2000 to obtain the carbon content in silicon-carbon materials. Theoretical true density of silicon ρ 硅 2.34 g / cm 3 , the theoretical true density of carbon ρ 碳 2.26g / cm 3 According to the calculation formula: V1 = 1 / ρ 真 -1 / (w 硅 ×ρ 硅 +w 碳 ×ρ 碳 ) to calculate the pore volume V1 of the closed pores.
[0283] ⑤Porous structure quantity test:
[0284] The test instrument used is ASAP2460-physical adsorption analyzer. The carbon particle samples after drying and degassing are placed in liquid nitrogen. Different test pressures are adjusted to measure the adsorption of nitrogen, and the adsorption and desorption isotherms are drawn. The shape of the pores is determined according to the shape of the hysteresis loop, and the pore distribution is calculated according to different pore models. The pore size distribution curve of the mesopore is fitted using the BJH model, and the pore size distribution curve of the micropore is fitted using the DFT model. Then it is obtained by statistical calculation.
[0285] ⑥ Pore size test of porous structure:
[0286] In the above ⑤ test on the number of porous structures, the pore size distribution curve of each pore is obtained, the specific surface area is obtained in ②, and the pore volume is obtained in ③. According to the model of the relevant pores in ⑤, the average pore size is obtained by dividing the pore volume by the specific surface area and multiplying by the model coefficient.
[0287] ⑦ Silicon grain size test:
[0288] Obtain the X-ray diffraction pattern of silicon-carbon material and calculate it using the Scherrer formula.
[0289] ⑧Tap density test:
[0290] Reference standard GB / T5162-2006.
[0291] ⑨Compacted density test under 5 tons:
[0292] Reference standard GB / T 24533-2009: measured using an electronic pressure tester (such as UTM7305). Specifically, a specific amount M of the powder sample to be tested is placed on a special pressing die (bottom area is S0) and different pressures are set. Each pressure is maintained for 30 seconds and then released. After 10 seconds, the thickness H0 of the powder pressed under the pressure (5 tons) is read on the device. The compaction density under the pressure is obtained by calculation, and the compaction density of the negative plate material under the pressure is equal to M / (H0×S0).
[0293] ⑩Powder resistivity test under 4Mpa:
[0294] Place an appropriate amount of silicon-carbon material in the feeding cup of the resistivity tester, apply pressure, collect data manually, record the powder resistivity test results at different pressure points and then take the average value. The test pressure is 4 MPa.
[0295] Table 1 Properties of porous carbon substrates (I)
[0296]
[0297]
[0298] Table 2 Properties of porous carbon substrates (II)
[0299]
[0300] Table 3 Ratios between the grain size d1 of nano-silicon grains and the average pore size d2 of porous carbon materials (III)
[0301]
[0302] Table 4 Process parameter list (IV)
[0303]
[0304]
[0305] Table 5 List of silicon-carbon materials of the embodiments and comparative examples
[0306]
[0307]
[0308] [Preparation of button cells]
[0309] 1. Negative electrode:
[0310] The silicon-carbon composite material, conductive carbon black and binder polyacrylic acid prepared above are mixed in a mass ratio of 8:1:1, and deionized water is added and stirred to form a negative electrode slurry; the negative electrode slurry is evenly coated on one surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.
[0311] 2. Electrolyte:
[0312] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 20:20:60, and then LiPF6 is uniformly dissolved in the above solution, and an additive fluoroethylene carbonate (FEC) is added to obtain an electrolyte. In the electrolyte, the concentration of LiPF6 is 1 mol / L, and the mass proportion of FEC in the electrolyte is 5%.
[0313] 3. Isolation film
[0314] Polyethylene film is used as the isolation membrane.
[0315] 4. Preparation of button cells
[0316] The negative electrode sheet is used as the working electrode and the metallic lithium is used as the counter electrode. The negative electrode sheet, the isolation membrane and the metallic lithium are stacked in order so that the isolation membrane is between the working electrode and the counter electrode, and the electrolyte is injected to assemble a CR2430 button cell.
[0317] (1) Test of the first lithium removal specific capacity and the first coulombic efficiency:
[0318] The above CR2430 button cell was subjected to the first charge and discharge test. At 25°C, it was discharged to 5 mV using a 0.05C constant current, left to stand for 10 min, and charged to 2.0 V using 0.1C to obtain the first discharge capacity and the first charge capacity.
[0319] The first delithiation specific capacity = the first delithiation capacity / the mass of the active material; wherein, the first delithiation capacity is also the first discharge capacity.
[0320] First coulombic efficiency = first discharge capacity / first charge capacity × 100%.
[0321] (2) Charge and discharge curve test:
[0322] The charge and discharge curve test of the above-mentioned CR2430 button battery is drawn. At 25°C, the charge and discharge voltage is 0.005~2.0V, and the charge and discharge capacity and the working electrode potential are differentiated to obtain a dQ / dV curve; specifically, 0.05C constant current discharge is used to discharge to 5mV, 50μA is used to discharge to 5mV, and it is allowed to stand for 10min, and 0.1C is used to charge to 2.0V; a curve graph of the relationship between the differential value dQ / dV obtained by differentiating the charge and discharge capacity Q by the working electrode potential V and the working electrode potential V is drawn.
[0323] In this dQ / dV curve, I1 is the peak intensity near 0.3V to 0.35V; I2 is the peak intensity near 0.43V to 0.50V;
[0324] Satisfies: Calculate R=I1 / I2.
[0325] The performance test results of the negative electrode are shown in Table 6.
[0326] Table 6 Performance list of negative electrode
[0327]
[0328] [Preparation of negative electrode sheet]
[0329] The silicon-carbon materials prepared in Examples 1 to 16 and Comparative Examples 1 and 2 are mixed with artificial graphite, binder styrene-butadiene rubber (SBR), binder polyacrylic acid (PAA), dispersant (CMC-Na), conductive carbon black (Super-P, SP), and carbon nanotubes (CNT) in a mass ratio of 20%: 75%: 2%: 1%: 1%: 0.7%: 0.3% and deionized water to form a uniformly stirred slurry, the slurry is defoamed, and then uniformly coated on the negative electrode current collector copper foil at a coating speed of 50 m / min and a coating mass of 130 mg / 1540.25 mm2 The temperature settings of the nine-section oven are 100℃ / 100℃ / 95℃ / 85℃ / 85℃ / 80℃ / 80℃ / 80℃ / 60℃ respectively; a cold press is used to compact the negative electrode sheet to a certain density to obtain a negative electrode sheet.
[0330] [Preparation of positive electrode sheet]
[0331] Taking lithium-ion batteries as an example, the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), binder polyvinylidene fluoride (PVDF), and conductive agent acetylene black are stirred and dispersed in N-methylpyrrolidone in a mass ratio of 97%:1.5%:1.5% to prepare a positive electrode slurry, which is then coated on the positive electrode current collector aluminum foil and compacted by a cold press to obtain a positive electrode sheet.
[0332] [Select a barrier film]
[0333] A polyethylene porous membrane with a thickness of 12 μm was selected.
[0334] [Select electrolyte]
[0335] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte. In the electrolyte, the concentration of LiPF6 is 1 mol / L.
[0336] [Battery formation]
[0337] According to some embodiments of the present application, the prepared negative electrode sheet, the isolation membrane and the positive electrode sheet are stacked in order, so that the isolation membrane is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, which is then inserted into a battery casing, and a lithium-ion secondary battery is obtained through processes such as baking, liquid injection, standing, packaging, formation, and capacity division.
[0338] [Performance test of secondary batteries]
[0339] (3) Cyclic performance test at 45°C:
[0340] The prepared secondary battery was charged at a constant current of 1C rate to a voltage of 4.25V at a constant temperature of 45°C, then charged at a constant voltage of 4.25V to a current of less than or equal to 0.05mA, then left to stand for 5 minutes, and then discharged at a constant current of 1C rate to a voltage of 2.5V, and left to stand for 5 minutes. This is a cycle charge and discharge process, and the discharge capacity of this time is recorded as the discharge capacity of the first cycle of the secondary battery. The secondary battery was subjected to a cyclic charge and discharge test according to the above method until the cycle capacity retention rate was 80%, which was recorded as the cycle life CL (45°C).
[0341] The 45°C cycle capacity retention rate of the secondary battery at the nth cycle at 45°C (%) = the discharge capacity at the nth cycle / the discharge capacity at the first cycle × 100%. Specific test results are shown in Table 6.
[0342] (4) Electrode cyclic expansion performance test at 45°C:
[0343] The thickness of the negative electrode of the secondary battery after the cold pressing process is recorded as h0. According to the above battery cycle performance test method at 45°C, the secondary battery is cycled 300 times, charged at a constant current rate of 1C to a voltage of 4.25V, and then charged at a constant voltage at a voltage of 4.25V to a current of less than or equal to 0.05mA, and then left to stand for 5 minutes. The cycled battery cell is disassembled in a dry room, and the thickness of the negative electrode after 300 cycles is recorded as h300, and the expansion rate of the secondary battery at 45°C for 300 cycles is Δh300.
[0344] Δh300(%)=(h300-h0) / h0×100%. Specific test results are shown in Table 7.
[0345] Table 7 Battery performance list
[0346]
[0347]
[0348] In combination with the above list, it can be seen that, in combination with Examples 1 to 16, the battery cycle performance of each embodiment that meets the scope of the list of this application has been improved to a certain extent. This may be due to the fact that the silicon-carbon material provided by this application is improved from multiple levels, such as forming nano-silicon grains with a certain suitable particle size, physical isolation, physical restriction, etc., while controlling the degree of expansion of the silicon material during the process of lithium ion insertion and extraction, thereby reducing the probability of side reactions between the silicon material and the electrolyte, thereby improving the cyclability of the battery to a certain extent.
[0349] Combined with Comparative Example 1, it can be seen that the size of the nano-silicon grains has a great influence on the battery. If the size of the nano-silicon grains cannot be reasonably matched with the aperture of the through hole, it is easy to cause the side reaction to increase and the material expansion to worsen.
[0350] It can be seen from Comparative Example 1, Comparative Example 2 and the embodiment that the presence of the silicon carbide material layer can significantly limit the expansion of the silicon material.
[0351] Therefore, on the one hand, the present application controls the size of nano-silicon grains to an appropriate level and reasonably matches them with the through holes, and on the other hand, limits the expansion size of silicon grains (such as setting closed holes, such as designing a silicon carbide material layer) to improve the cycle performance of the battery.
[0352] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A silicon-carbon material, characterized in that: include: Silicon-carbon composite particles, the silicon-carbon composite particles comprising: Porous carbon materials: have through holes; Nano silicon crystal grains: located in the through holes; the grain size of the nano silicon crystal grains is not less than the average pore size of the porous carbon material; The silicon carbide material layer is at least partially located on the wall of the through hole.
2. The silicon-carbon material according to claim 1, characterized in that: The grain size of the nano-silicon grains is d1, and the average pore size of the porous carbon material is d2, satisfying: d1 / d2=1~15.
3. The silicon-carbon material according to claim 2, characterized in that: The grain size of the nano-silicon grains is d1, and the average pore size of the porous carbon material is d2, satisfying: d1 / d2=2~10.
4. The silicon-carbon material according to any one of claims 1 to 3, characterized in that: The grain size of the nano-silicon grains is d1, d1≥5nm; and / or; The average pore diameter of the porous carbon material is d2, and d2 is 1.0 nm to 5.0 nm.
5. The silicon-carbon material according to claim 4, characterized in that: The grain size of the nano-silicon grains is d1, and d1 is 5nm to 20nm; and / or; The average pore diameter of the porous carbon material is d2, and d2 is 1.5nm to 5.0nm.
6. The silicon-carbon material according to any one of claims 1 to 5, characterized in that: The silicon-carbon composite particles include closed pores, and the pore volume of the closed pores is smaller than the pore volume of the through pores.
7. The silicon-carbon material according to claim 6, characterized in that: The silicon-carbon composite particles include closed pores, the pore volume of the closed pores is V1, and the pore volume of the through pores is V2. Satisfies: V2 / V1=5~24.
8. The silicon-carbon material according to claim 7, characterized in that: The silicon-carbon composite particles include closed pores, the pore volume of the closed pores is V1, and the pore volume of the through pores is V2, satisfying: V2 / V1=7-16.
9. The silicon-carbon material according to claim 6, characterized in that: The pore volume of the closed pore is V1, and V1 is 0.04 cm 3 / g~0.16cm 3 / g; and / or; The pore volume of the through hole is V2, and V2 is 0.3 cm 3 / g~1.5cm 3 / g.
10. The silicon-carbon material according to any one of claims 1 to 9, characterized in that: The through holes include micropores, mesopores and macropores, and based on the total volume of the through holes, the volume ratio of the micropores, the mesopores and the macropores is (40% to 95%): (5% to 50%): (0 to 15%).
11. The silicon-carbon material according to any one of claims 1 to 10, characterized in that: The silicon carbide material layer is located between the through hole and the nano-silicon grains, wherein one side of the silicon carbide material layer is connected to the inner wall of the through hole, and the other side of the silicon carbide material layer is connected to the nano-silicon grains.
12. The silicon-carbon material according to claim 11, characterized in that: The thickness of the silicon carbide material layer is less than 0.7 nm.
13. The silicon-carbon material according to any one of claims 1 to 12, characterized in that: The silicon-carbon material further includes a carbon coating layer, and the carbon coating layer is arranged along the outer surface of the porous carbon material.
14. The silicon-carbon material according to any one of claims 1 to 13, characterized in that: The porous carbon material comprises porous carbon particles, and the porous carbon particles meet the following conditions: (1.1) The volume distribution particle size of the porous carbon particles satisfies: Dv50 is 3.0 μm to 6.5 μm; Dv90 is 13.5 μm to 18.5 μm; Dv10 is 0.9 μm to 2.5 μm; (1.2) The specific surface area of the porous carbon particles is 900 m 2 / g~1550m 2 / g; (1.3) The tap density of the porous carbon particles is 0.22 g / cm 3 ~0.48g / cm 3 ; (1.4) The compacted density of 5 tons of porous carbon particles is 0.45 g / cm 3 ~0.80g / cm 3 .
15. The silicon-carbon material according to claim 14, characterized in that: The porous carbon material comprises porous carbon particles, and the porous carbon particles satisfy at least one of the following requirements: (2.1) The volume distribution particle size of the porous carbon particles satisfies: Dv50 is 3.5 μm to 6.0 μm; Dv90 is 14.0 μm to 18.0 μm; Dv10 is 1.0 μm to 2.0 μm; (2.2) The specific surface area of the porous carbon particles is 1000 m 2 / g~1500m 2 / g; (2.3) The tap density of the porous carbon particles is 0.25 g / cm 3 ~0.45g / cm 3 ; (2.4) The compacted density of 5 tons of porous carbon particles is 0.50 g / cm 3 ~0.75g / cm 3 .
16. The silicon-carbon material according to any one of claims 1 to 15, characterized in that: Based on the total mass of the silicon-carbon material, the mass percentage content of silicon in the silicon-carbon material is w 硅 , satisfying: w 硅 It is 38.0% to 48.0%.
17. The silicon-carbon material according to any one of claims 1 to 16, characterized in that: The silicon-carbon composite particles meet the following conditions: (3.1) The volume distribution particle size of the silicon-carbon composite particles satisfies: (Dv90-Dv10) / Dv50 is 1.2 to 2.8; (3.2) The specific surface area of the silicon-carbon composite particles is 3.0 m 2 / g~12.0m 2 / g; (3.3) The tap density of the silicon-carbon composite particles is 0.5 g / cm 3 ~1.0g / cm 3 ; (3.4) The compacted density of 5 tons of the silicon-carbon composite particles is 0.80 g / cm 3 ~1.1g / cm 3 .
18. The silicon-carbon material according to claim 17, characterized in that: The silicon-carbon composite particles satisfy at least one of the following requirements: (4.1) The volume distribution particle size of the silicon-carbon composite particles meets the following requirements: Dv50 is 3.5 μm to 9.0 μm; Dv90 is 14.0 μm to 21.0 μm; Dv10 is 0.9 μm to 3.0 μm; (4.2) The specific surface area of the silicon-carbon composite particles is 5.0 m 2 / g~10.0m 2 / g; (4.3) The tap density of the silicon-carbon composite particles is 0.6 g / cm 3 ~0.8g / cm 3 ; (4.4) The compacted density of 5 tons of the silicon-carbon composite particles is 0.90 g / cm 3 ~1.05g / cm 3 .
19. The silicon-carbon material according to any one of claims 1 to 18, characterized in that: The properties of the silicon-carbon composite particles are as follows: The powder resistivity of the silicon-carbon composite particles at 4 MPa is 1.30 Ω·cm to 3.80 Ω·cm; and / or; The lithium removal specific capacity of the silicon-carbon composite particles is 1300mAh / g to 1500mAh / g, and the first coulombic efficiency is 77% to 81%; and / or; In the dQ / dV curve of the silicon-carbon composite particles, I1 is the peak intensity near 0.3V~0.35V; I2 is the peak intensity near 0.43V~0.50V; it satisfies: I1 / I2=1.4~1.8; the dQ / dV curve of the silicon-carbon composite particles includes the silicon-carbon composite particles as the positive electrode active material, the metal lithium sheet as the counter electrode, assembled to form a CR2430 button battery, at 25°C, the charge and discharge voltage is 0.005V~2.0V, and the charge and discharge capacity and the working electrode potential are obtained by differential processing.
20. A method for preparing the silicon-carbon material according to any one of claims 1 to 19, characterized in that: include: providing a porous carbon substrate; Introducing a silicon source into the porous carbon substrate to generate a porous carbon material comprising nano-silicon grains and a silicon carbide material layer; A carbon source is introduced into the porous carbon material comprising nano-silicon grains and a silicon carbide material layer to generate a silicon-carbon material comprising a carbon coating layer.
21. The method for preparing a silicon-carbon material according to claim 20, characterized in that: The reaction conditions for generating the porous carbon material comprising nano-silicon grains and a silicon carbide material layer are as follows: (5.1) The reaction temperature is 500°C to 700°C, and the silicon source is introduced for 3h to 42h; (5.2) The silicon source comprises a silicon source gas and a dilution gas, wherein the volume percentage of the silicon source gas is 15% to 95%; the silicon source gas comprises either or both of monosilane and disilane; (5.3) The ventilation volume of the silicon source is 0.2L / min to 1.5L / min.
22. The method for preparing a silicon-carbon negative electrode material according to any one of claims 20 to 21, characterized in that: The porous carbon substrate comprises carbon, oxygen and nitrogen, and the mass ratio of the carbon to the oxygen and nitrogen is (94% to 97%): (2% to 4%): (1% to 2%); And / or; the ash content of the porous carbon substrate is ≤0.5%.
23. A secondary battery comprising a negative electrode plate, characterized in that: The negative electrode plate comprises the silicon-carbon negative electrode material according to any one of claims 1 to 19 or the silicon-carbon material prepared by the preparation method according to any one of claims 20 to 22.
24. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 23.
Citation Information
Patent Citations
Silicon-carbon composite material and preparation method thereof, secondary battery and electric device
CN117096330A
Silicon-carbon composite material and preparation method thereof, negative pole piece, secondary battery and electric device
CN117174882A
Silicon-based electrode active material for secondary battery
CN117199285A
Composite material for secondary lithium ion battery as well as preparation method and application of composite material
CN117558888A
Silicon-carbon negative electrode material, battery negative electrode, battery and preparation method of silicon-carbon negative electrode material
CN117613233A
Cited By
Battery cell, silicon-carbon composite material and preparation method, battery device, and electric device
WO2026036694A1